FORMULASI PAKAN TERNAK SAPI PERAH BERBAHAN DASAR BLOTONG, TONGKOL JAGUNG, DAN TEPUNG IKAN KUALITAS RENDAH DENGAN PENAMBAHAN PROBIOTIK - Euginius Eduard Effendi; Ruth Chrisnasari; Tjandra Pantjajani (Perpustakaan Universitas Surabaya, 2018)
Cattle feed is a product made from a variety of organic compounds that are useful as a staple food of cattle. Filter cake usually called blotong is solid mud from the sugar mill industrial. Corn cob is an agriculture waste. Low quality fish flour is fish waste which is dried and milled. Cattle feed formulation made from raw materials has a completeness in meeting the nutritional needs of dairy cattle feed. The three ingredients processed into animal feed formulations to find the best and qualify the Indonesian National Standard (SNI). The best formulation with the composition of the filter cake 30%, 30% corn cobs, and low quality fish flour 40%. The formulation has a reduced sugar content of 0,21%, 1,6% total sugar, 4,23% water, 8,48% ash, 21,69% crude fiber, 21.3% protein, 1.84% fat, and pH of 6.39. Best cattle feed formulation was fermented by Lactobacillus acidophilusuntil seven days. After observation, reduced sugar content, total sugar, crude fiber, and pH were decreased. Probiotics was determined using Total Plate Count with the number of cells 6,12x1010 on the seventh day of fermentation.